The Dobrushin ergodicity coefficient and the ergodicity of noncommutative Markov chains - Mukhamedov, Farrukh (Elsevier, 2013)
In this paper, we study the notion of the Dobrushin ergodicity coefficient for positive contractions defined on the predual M∗ of von Neumann algebra M. Moreover, in terms of this coefficient, we prove ergodic-type theorems for nonhomogeneous Markov chains on M∗.